2003
DOI: 10.1128/aac.47.12.3768-3773.2003
|View full text |Cite
|
Sign up to set email alerts
|

Efficacies of Vancomycin, Arbekacin, and GentamicinAlone or in Combination against Methicillin-Resistant Staphylococcus aureus in an In Vitro InfectiveEndocarditisModel

Abstract: We adopted an in vitro infective endocarditis model (IVIEM) to compare the efficacy of vancomycin (VAN), arbekacin (ABK), and gentamicin (GEN) alone or in combination. Using two strains of clinically isolated methicillin-resistant Staphylococcus aureus, one GEN susceptible (GS171) and one GEN resistant (GR153), fibrin clots were prepared and suspended in the IVIEM. Antibiotics were given as boluses every 6 h (q6h), q12h, or q24h or by continuous infusion with VAN, q12h or q24h with ABK, and q8h or q24h with GE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…Arbekacin is a derivative of aminoglycoside dibekacin, and it has been reported with a good in vitro activity against MRSA [19, 20]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arbekacin is a derivative of aminoglycoside dibekacin, and it has been reported with a good in vitro activity against MRSA [19, 20]. …”
Section: Discussionmentioning
confidence: 99%
“…Lee et al reported that an arbekacin based combination therapy can substitute glycopeptide antibiotics for the treatment of MRSA or hetero-VISA infections, and the study concluded that there was no difference in the clinical efficacy between arbekacin and vancomycin [20]. …”
Section: Discussionmentioning
confidence: 99%
“…GEN was administered via syringes connected to the central compartment. The simulated GEN regimens were as follows: 80 mg every 8 hours (q8h, peak concentration 5 mg/L, half-life 2 hours) and 240 mg every 24 hours (q24h, peak concentration 15 mg/L, half-life 2 hours) 4,20. Before starting the experiment, 10 minutes passed before reaching the equilibrium of GEN concentration between central and peripheral compartment.…”
Section: Methodsmentioning
confidence: 99%
“…The earlier work from the Rybak group (Palmer and Rybak 1996 ;LaPlante and Rybak 2004 ;Tsuji and Rybak 2005 ) showed essentially no difference between the resistant and susceptible strains that they studied. Lee et al employed the SEV model to show that vancomycin killing was enhanced by arbekacin and gentamicin whether or not the strain was susceptible to gentamicin (Lee et al 2003 ), although the killing at 72 h was not greater than that with arbekacin alone. Recently, the novel combination of trimethoprimsulfamethoxazole with daptomycin has been shown to synergistic with daptomycin in the SEV model against strains of S. aureus with reduced susceptibility to daptomycin (Steed et al 2010 ).…”
Section: Staphylococcimentioning
confidence: 99%